Pemikiran Ibnu Malik tentang Istisyhad dengan Hadis dalam Masalah Nahwu - Eka Rizal (Universitas Yudharta Pasuruan, 2021)
This article discusses Ibnu Malik's thoughts on the use of hadith as a martyr and a proposition in determining the rules of nahwu. This research is qualitative in nature which relies on primary data taken from the books of nahwu by Ibnu Malik and secondary data in the form of syarah books from the book of Ibnu Malik. This study reveals the reasons for Ibnu Malik in establishing the hadith as a valid martyr based on the Prophet's fluency in Arabic, Ibnu Malik's method of performing istisyhad with hadith, several examples of Ibnu Malik's istisyhad with hadith and the responses of scholars after Ibnu Malik about istisyhad with hadith. This study also tries to examine the narrated hadith with the meaning and lahn which contained in the hadith which is used as an excuse by scholars who discard the hadith with the hadith in the discussion of nahwu.